Die nagmaal as middelruimte tussen ryk en arm gelowiges om sigbaarheid aan versoening in die samelewing te gee. - Taljaard, A (Nederduitse Gereformeerde Teologiese Tydskrif, 2004)
The Eucharist as middle space between rich and poor believers to embody reconciliation in society The gap between the eschatological vision of reconciliation and the realities of social and political life cannot be bridged by words alone, but only by word that take on flesh and concreteness (De Gruchy 2002:75). I therefore propose a structure, a concreteness that could become a reconcile-reality between the rich and the poor, the structure being the middle space as the Eucharist. This article underlines the importance of the recognising of the unjust system and the acknowledgment of fellow human beings as our neighbours, our bothers and sisters. The article also shows that the relationship “between us” needs exploration. It then clarifies this space between us, by revering to the work of the South African artist Williamson and the narrative “Disgrace”. These works show within the South African context how time, the middle space and dialogue challenge and influence this relationship between us. In the light of this example, I propose then that the Eucharist could become the middle space where believers meet and where time and dialogue are transformed. Therefore, this middle space could open up the possibility firstly, to realise and to act our responsibility towards one another and secondly to embody this reconciliation and restorative justice in society.